2016
DOI: 10.1016/j.corsci.2016.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal cations on corrosion of mild steel in model fresh water

Abstract: The effects of metal cations on corrosion of mild steel in model fresh water were investigated by electrochemical techniques and immersion tests. Analysis of X-ray photoelectron spectroscopy showed that metal cations have large hardness of cations, X, are incorporated in passive films. The electrochemical and immersion results showed that X is not suitable as a corrosion indicator of mild steel. A novel corrosion indicator, "corrosion inhibitory effect of cations Y", that consists of X and molar volume ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 26 publications
(32 reference statements)
4
48
0
Order By: Relevance
“…These clear grain boundaries mean that intense uniform corrosion occurred on the mild steel in NaA solution. 26 Pits on the specimen are observed after immersion in NaG solution ( Fig. 2 (c)).…”
Section: Surface Sem Imagesmentioning
confidence: 99%
See 4 more Smart Citations
“…These clear grain boundaries mean that intense uniform corrosion occurred on the mild steel in NaA solution. 26 Pits on the specimen are observed after immersion in NaG solution ( Fig. 2 (c)).…”
Section: Surface Sem Imagesmentioning
confidence: 99%
“…9 (d)). It has been also shown that metal cations that have large ∆V would form the defectless and highly protective layer on mild steel, 26 therefore, the metal cation layer of Zn 2+ would have good protective ability against Cl -attack in the solution. For these reasons, Zn 2+ with large Y would contribute to the enhancement of the inhibition ability of gluconates for mild steel in fresh water.…”
Section: Model Of the Enhancement Of Corrosion Inhibition Ability Of mentioning
confidence: 99%
See 3 more Smart Citations